Aplikasi IoT Pemantauan Detak Jantung Pasien Lansia Beresiko Tinggi di RSCM Cut Mutia Lhokseumawe Berbasis Mobile - Ananda Faridhatul Ulva; Nurdin; Rizky Putra Fhonna; Desvina Yulisda; Muzakir Nur; Rizki Setiawan (Universitas Islam Raden Rahmat, Malang, 2023)
Monitoring the health of the elderly is very necessary, this monitoring must be carried out periodically and in real time using a genetic algorithm, so as to increase the guarantee of the safety and welfare of the elderly population and can be a preventive action to anticipate things that you want to avoid. However, sometimes the distance between the patient and RSCM Cut Mutia Lhokseumawe is quite far, and handlers are not responsive enough to make it difficult for elderly families to receive early treatment. The method for creating an IoT application for monitoring elderly heart rate using the waterfall method, for a decision-making system for high-risk patient systems using a Genetic Algorithm. The expected result of this application is remote monitoring with rapid response in the form of an IoT Heartbeat tool that is used in the elderly, so that if elderly patients experience heart failure, the system will quickly respond to receive messages about what is felt by the elderly, through the IoT style used elderly and decision making system using a genetic algorithm